A critical analysis of the South African Income Tax Act with regards to the taxation of financial instruments: in particular derivatives - Maoke, Mohale (My University, 2021)
The past two decades has seen the rise in popularity and usage of derivative instruments. During this period, financial engineering has advanced by leaps and bounds. Corporates use some form of financial innovation which includes the use of derivative instruments in their tax planning. The use of derivatives instruments results can result in a set of complex taxing problems. This includes but is not limited to problems in identifying the characteristic of the derivative income. This has often brought about the question of whether global tax authorities have been kept up with the advancements in derivative instruments. This increase in popularity has not gone unnoticed in South Africa which has resulted in a several academic studies undertaken regarding the challenges that emanate from the usage of these derivative instruments from a taxation perspective (Jabulani Masondo, 2009; Annette Wanyana Oguttu, 2012; Rohan Kruger, 2015, to name a few). South Africa since then enacted significant legislation for the taxation of financial instruments as well as anti-avoidance provision. The aim of this research is to review the taxation of financial instruments, in particularly derivatives in terms of Income Tax Act 58 of 1962 (“the ITA”) in the context of practical examples. The research will use the application of the general taxation principles, anti-avoidance provisions and case law on the taxation of derivative instruments.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Taxation) to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2021